A Comprehensive Literature Review of the use of The Bakri Balloon for Managing Postpartum Hemorrhage - Kowal, Joanna; Połujański, Paweł; Cyran, Piotr; Jaroszyńska, Anna; Jaroszyński, Filip; Paleczny, Jan; Parobczak, Robert; Winciorek, Joanna; Wiśniewska, Adrianna (Journal of Education, Health and Sport, 2024)
Postpartum hemorrhage (PPH) remains a significant cause of maternal mortality and morbidity worldwide. It is defined as excessive bleeding, typically more than 500 ml of blood loss within the first 24 hours after childbirth. The Bakri Balloon technique has emerged as a promising solution for managing PPH, offering a minimally invasive approach to achieving hemostasis and preventing the need for more invasive surgical procedures. Aims: The aim of this paper review is to provide an overview of the effectiveness of intrauterine balloon tamponade in managing PPH. Methods: We conducted this paper review by selecting articles, retrospective cohort studies and reviews from clinical trials from PubMed. Results: Numerous studies have shown high success rates of treating PPH using The Bakri Balloon intrauterine tamponade. Conclusions: The Bakri Balloon intrauterine tamponade is an effective method in the management of primary postpartum hemorrhage.